Novel treatment approach to the premature ovarian failure in women of reproductive age with pelvic inflammatory disease - N.A. Burova; T.A. Selezneva; O.V. Abolonina (РМЖ. Мать и дитя, 2019)
Novel treatment approach to the premature ovarian failure in women of reproductive age with pelvic inflammatory disease N.A. Burova1, T.A. Selezneva2, O.V. Abolonina1,2 1Volgograd State Medical University, Russian Federation 2 LLC “Healthcare Clinic “VitaNova”, Volgograd, Russian Federation Aim: to study the efficacy of menopausal hormone therapy in combination with low molecular weight water soluble polypeptides isolated from bovine pineal gland to reduce somatic and vegetative symptoms in women with neurovegetative disorders and low estrogen levels diagnosed with premature ovarian failure and chronic salpingoophoritis. Patients and methods: the study included 45 patients of reproductive age with secondary ovarian failure resulted from chronic pelvic inflammation (with secondary amenorrhea, infertility, increased gonadotropin levels, and vegetative vascular disorders). Changes in Blatt-Kupperman menopausal index (BKMI), autonomic reactivity, and hormonal profile as well as pelvic ultrasound results were analyzed. All patients were divided into two groups. Study group included 20 women who received menopausal hormone therapy (MHT) plus low molecular weight water soluble polypeptides isolated from bovine pineal gland (Pineamin®). Comparison group included 25 women who received MHT using Femoston® 2 (one tablet P.O., cyclically). Control group included 27 women. Final examination was performed in six months. Results: initial (i.e., before the treatment started) examination revealed hormonal imbalances (increased follicle-stimulating hormone levels and decreased estradiol levels) which is typical for premature ovarian failure resulted from chronic adnexal inflammation. Pelvic ultrasound revealed single follicles and decreased (by 2.5 times) ovarian volume as compared with healthy individuals. In addition, severe vegetative vascular symptoms and impaired regular interaction between brain cortex and subcortical structures were observed. MHT plus low molecular weight water soluble polypeptides isolated from bovine pineal gland resulted in significant decrease in BKMI (by 4.9 times) and follicle-stimulating hormone levels (by 7.2 times) as well as in the recovery of bioelectrical brain activity in 93% of the patients. Conclusion: complex medical therapy in patients with secondary ovarian failure and chronic salpingoophoritis resulted in increased ovarian volume, improved folliculogenesis and the mechanisms of its stimulation and, as a consequence, successful spontaneous and in vitro fertilization pregnancy. These findings allow to recommend Femoston® 2 plus Pineamin® for complex treatment for premature ovarian failure resulted from chronic salpingoophoritis. Key words: premature ovarian failure, chronic salpingoophoritis, neurovegetative disorders, Blatt-Kupperman menopausal index, menopausal hormone therapy, Pineamin. For citation: Burova N.A., Selezneva T.A., Abolonina O.V. Novel treatment approach to the premature ovarian failure in women of reproductive age with pelvic inflammatory disease. Russian Journal of Woman and Child Health. 2019;2(1):10–15.